2013
DOI: 10.1681/asn.2012090898
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Deletion and Regulatory T Cells Prevent Antimyeloperoxidase GN

Abstract: Loss of tolerance to neutrophil myeloperoxidase (MPO) underlies the development of ANCA-associated vasculitis and GN, but the mechanisms underlying this loss of tolerance are poorly understood. Here, we assessed the role of the thymus in deletion of autoreactive anti-MPO T cells and the importance of peripheral regulatory T cells in maintaining tolerance to MPO and protecting from GN. Thymic expression of MPO mRNA predominantly localized to medullary thymic epithelial cells. To assess the role of MPO in formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…These features may account for the uncommon recurrences of anti-GBM disease compared with other autoimmune glomerulonephritis (Wolf et al, 2005;Ooi et al, 2011;Tan et al, 2013). In this study, few Tregs were observed in the kidney.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…These features may account for the uncommon recurrences of anti-GBM disease compared with other autoimmune glomerulonephritis (Wolf et al, 2005;Ooi et al, 2011;Tan et al, 2013). In this study, few Tregs were observed in the kidney.…”
Section: Discussionmentioning
confidence: 50%
“…A few unique features of the T cell response to GBM include the appearance of long-living Tregs and the inversion of T cell effector/regulatory cell ratios in later stages of the disease in animal models (Wolf et al, 2005;Ooi et al, 2011;Tan et al, 2013). These features may account for the uncommon recurrences of anti-GBM disease compared with other autoimmune glomerulonephritis (Wolf et al, 2005;Ooi et al, 2011;Tan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tregs have an important protective role in kidney inflammatory diseases. In mouse models, Treg impairment has been associated with exacerbated disease in cisplatin-induced nephrotoxicity, [66] nephrotoxic nephritis (NTN), [67-72] anti-myeloperoxidase GN, [73] and ischemic acute kidney injury. [74-76] Furthermore, adoptive transfer of Tregs prior to induction of nephrotoxic nephritis significantly decreased kidney damage.…”
Section: Effector and Regulatory Immune Cells And The Renal Inflammatmentioning
confidence: 99%
“…The research group of Kitchen and Holdsworth [64,65,66,67] have used a mouse model to study potential pathogenic roles for T cells in AAV. They induced glomerulonephritis by immunizing mice with human MPO, which induced B- and T-cell autoimmunity to mouse MPO.…”
Section: T Cells In Anca Pathogenesismentioning
confidence: 99%
“…The same research group also showed the importance of T cells in the pathogenesis of their model of AAV by blocking the induction of MPO autoimmunity by impairing central thymic T cells or peripheral regulatory T cells [66], or by inducing tolerance to the nephritogenic MPO peptide by nasal insufflation of the peptide [67]. …”
Section: T Cells In Anca Pathogenesismentioning
confidence: 99%